Effect of Noncardiac Comorbidities on Quality of Life among Patients with Heart Failure - An Observational Study - J. Anusha; Vishwanath Krishnamurthy; Varun V. Prakash; Madhu P. Raj; H. Aadithya Shyllesh; G.R. Bharath (APIK Journal of Internal Medicine, 2025)
Introduction: Heart failure (HF) is frequently associated with multiple cardiac and noncardiac comorbidities, with most requiring active management. Various studies using multiple tools iterate the association between various components of quality of life (QoL) in HF patients. Identifying comorbidities and correlating QoL among HF patients would help improve the quality of care. Materials and Methods: In this cross-sectional study, among 158 HF patients aged >18 years, QoL was estimated using the Kansas City Cardiomyopathy Questionnaire (KCCQ) over a 2-week recall. Comorbidities were analyzed with ejection fraction (EF), and HF status. Associations with QoL were studied, and intergroup differences were analyzed using the ANOVA/Kruskal–Wallis test. For assessing statistical significance, P < 0.05 was considered statistically significant. Results: Among the 98 HF with reduced EF (HFrEF) patients and 60 HF with preserved EF (HFpEF) patients, female preponderance in the HFpEF group (53.3%) and males in the HFrEF group (68.4%) was noted. HFpEF was dominant in those aged 61–80. HFrEF patients were likelier to have hospital stay <10 days, and HFpEF patients, 10–20 days. Mean KCCQ scores were lower among HFpEF (36.10 vs. 41.74), as were mean values of hemoglobin (11.37 vs. 12.18 g%) and NTproBNP (6584.43 vs. 12088.77 pg/mL (P < 0.05); HFrEF was significantly associated with ischemic heart disease, antiplatelets, statins, and poorer QoL with chronic kidney disease. HFpEF was significantly associated with atrial fibrillation and obstructive sleep apnea, use of angiotensin-converting enzyme inhibitors and angiotensin receptor blocker, and poorer QoL with chronic obstructive pulmonary disease. Conclusion: Patients with HFpEF were observed to have a higher chance of comorbidities and poorer QoL.